Efficacy and safety of artificial urinary sphincter (AUS): Results of a large multi‐institutional cohort of patients with mid‐term follow‐up. Issue 2 (21st December 2018) - Tutolo, Manuela; Cornu, Jean‐Nicolas; Bauer, Ricarda M.; Ahyai, Sascha; Bozzini, Giorgio; Heesakkers, John; Drake, Marcus J.; Tikkinen, Kari A.O.; Launonen, Ene; Larré, Stéphane; Thiruchelvam, Nikesh; Lee, Richard; et al.
Abstract : Aims: To assess efficacy and safety as well as predictive factors of dry rate and freedom from surgical revision in patients underwent AUS placement. The artificial urinary sphincter (AUS) is still considered the standard for the treatment of moderate to severe post‐prostatectomy stress urinary incontinence (SUI). However, data reporting efficacy and safety from large series are lacking. Methods: A multicenter, retrospective study was conducted in 16 centers in Europe and USA. Only primary cases of AUS implantation in non‐neurogenic SUI after prostate surgery, with a follow‐up of at least 1 year were included. Efficacy data (continence rate, based on pad usage) and safety data (revision rate in case of infection and erosion, as well as atrophy or mechanical failure) were collected. Multivariable analyses were performed in order to investigate possible predictors of the aforementioned outcomes. Results: Eight hundred ninety‐two men had primary AUS implantation. At 32 months mean follow‐up overall dry rate and surgical revision were 58% and 30.7%, respectively. Logistic regression analysis showed that patients without previous incontinence surgery had a higher probability to be dry after AUS implantation (OR: 0.51, P = 0.03). Moreover institutional case‐load was positively associated with dry rate (OR: 1.18; P = 0.005) and freedom from revision (OR: 1.51; P = 0.00). Conclusions: The results of this study showed that AUS is an effective option for the treatment of SUI after prostate surgery. Moreover previous incontinence surgery and low institutional case‐load are negatively associated to efficacy and safety outcomes.